Profil Distribusi Apotek di Kabupaten Banyumas berdasarkan Sistem Informasi Geografi dan Korelasinya dengan Jumlah Kunjungan dan Resep Tahun 2019 - Manan, Abdul; Utami, Pri Iswati; Siswanto, Agus (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
The distribution of pharmacies in Indonesia is still becoming a problem. Pharmacies are mostly available around healthcare facilities such as hospitals, service providers, trade centers, transportation facilities, and main roads. The study aims to describe the distribution profile of pharmacies based on Geographic Information System (GIS) analysis and to study the relation between pharmacy distribution profiles with the number of consumer visits and prescriptions. The study is conducted in 27 sub-districts in Banyumas Regency, Central Java using Arc Gis 3.10.2 Software. Pharmacy profile, the number of consumer visits, and prescriptions at the pharmacy are obtained by distributing research questionnaires to pharmacists. The results showed that the distribution of pharmacies in the Banyumas Regency was still dominant in urban areas, which reached 55%. The average distance of pharmacies was 2.34 km. The research results on the distribution pattern of pharmacies in 27 sub-districts showed that in 3 districts (11.1%) were grouped in certain areas, in 24 other districts (88.9%), the pharmacies' distribution had a spread distribution pattern. The conclusion of the research that the distribution of pharmacies in the Banyumas Regency based on GIS visualization was still dominant in urban areas and especially in sub-districts around the capital of Banyumas Regency, Purwokerto. Based on the study, there was a relation between the average distance of pharmacies and the number of healthcare facilities on consumer visits. There was a relation between pharmacy density, population density, and the number of healthcare facilities with the number of prescriptions.